FENOMENA CANCEL CULTURE DI INDONESIA: SEBUAH TINJAUAN LITERATUR - Altamira, Melisa Bunga; Movementi, Satwika Gemala (UI Scholars Hub, 2023)
The phenomenon and terminology of cancel culture is currently being discussed in Indonesia. The echo of cancel culture is expanding along with the increase of social media users. Through social media, the movement of cancel culture is disseminated. This study describes the phenomenon of cancel culture in Indonesia compared to several other countries, along with the impacts. Research and discussion on cultural cancellation in a global context have been widely published. However, research and discussion on the cultural cancellation in Indonesia have yet been sufficient. This study aims to describe the phenomenon of cancel culture in Indonesia using a descriptive methodology through literature review (range 2018-2021). The results show that cancel culture in Indonesia is still a new phenomenon and closely related to social media. Celebrities are public figures that most affected by the cancel culture, both those who appear in the mass media and social media. This research is expected to provide a new understanding of the phenomenon that occurs in aborted culture and recommendations regarding the importance of consideration in conveying to the public. In addition, this study can be used as a recommendation for the policy-makers to elevate the level of digital literacy.